An endovaginal MRI array with a forward‐looking coil for advanced gynecological cancer brachytherapy procedures: Design and initial results. Issue 11 (8th October 2021) - Alipour, Akbar; Viswanathan, Akila N.; Watkins, Ronald D.; Elahi, Hassan; Loew, Wolfgang; Meyer, Eric; Morcos, Marc; Halperin, Henry R.; Schmidt, Ehud J.
Abstract: Purpose: To develop an endovaginal MRI array that provides signal enhancement forward into the posterior parametrium and sideways into the vaginal wall, accelerating multiple‐contrast detection of residual tumors that survive external beam radiation. The array's enclosure should form an obturator for cervical cancer brachytherapy, allowing integration with MRI‐guided catheter placement, CT, and interstitial radiation dose delivery. Methods: The endovaginal array consisted of forward‐looking and sideways‐looking components. The forward‐looking element imaged the cervix and posterior endometrium, and the sideways‐looking elements imaged the vaginal wall. Electromagnetic simulation was performed to optimize the geometry of a forward‐looking coil placed on a conductive‐metallic substrate, extending the forward penetration above the coil's tip. Thereafter, an endovaginal array with one forward‐looking coil and four sideways‐looking elements was constructed and tested at 1.5 Tesla in saline and gel phantoms, and three sexually mature swine. Each coil's tuning, matching, and decoupling were optimized theoretically, implemented with electronic circuits, and validated with network‐analyzer measurements. The array enclosure emulates a conventional brachytherapy obturator, allowing use of the internal imaging array together with tandem coils and interstitial catheters, as well as use of the enclosure alone during CT and radiation delivery. To evaluate the receive magnetic field ( B 1 − ) spatial profile, the endovaginal array's specific absorption‐rate (SAR) distribution was simulated inside a gel ASTM phantom to determine extreme heating locations in advance of a heating test. Heating tests were then performed during high SAR imaging in a gel phantom at the predetermined locations, testing compliance with MRI safety standards. To assess array imaging performance, signal‐to‐noise‐ratios (SNR) were calculated in a saline phantom and in vivo. Swine images were acquired with the endovaginal array combined with the scanner's body and spine arrays. Results: Simulated B 1 − profiles for the forward‐looking lobe pattern, obtained while varying several geometric parameters, disclosed that a forward‐looking coil placed on a metal‐backed substrate could double the effective forward penetration from approximately 25 to ∼40 mm. An endovaginal array, enclosed in an obturator enclosure was then constructed, with all coils tuned, matched, and decoupled. The ASTM gel‐phantom SAR test showed that peak local SAR was 1.2 W/kg in the forward‐looking coil and 0.3 W/kg in the sideways‐looking elements, well within ASTM/FDA/IEC guidelines. A 15‐min 4 W/kg average SAR imaging experiment resulted in less than 2 o C temperature increase, also within ASTM/FDA/IEC heating limits. In a saline phantom, the forward‐looking coil and sideways‐looking array's SNR was four to eight times, over a 20–30 mm field‐of‐view (FOV), and five to eight times, over a 15–25 mm FOV, relative to the spine array's SNR, respectively. In three sexually mature swine, the forward‐looking coil provided a 5 + 0.2 SNR enhancement factor within the cervix and posterior endometrium, and the sideways‐looking array provided a 4 + 0.2 SNR gain factor in the vaginal wall, relative to the Siemens spine array, demonstrating that the array could significantly reduce imaging time. Conclusions: Higher SNR gynecological imaging is supported by forward‐looking and sideways‐looking coils. A forward‐looking endovaginal coil for cervix and parametrium imaging was built with optimized metal backing. Array placement within an obturator enhanced integration with the brachytherapy procedure and accelerated imaging for detecting postexternal‐beam residual tumors.